Understanding Inclusion, Diversity, Equity, and Accessibility in a Distributed Data Network: Environmental Scan Within Health Data Research Network Canada - Freier, Amy; Bowler, Laura; Owczar, Hannah; Gogovor, Amédé; Pandey, Mamata; Riley, John; Stirling, Morgan; Duris, Jessica; McGrail, Kimberlyn; Nickel, Nathan (International Journal of Population Data Science, 2026)
Inclusion, Diversity, Equity, and Accessibility (IDEA) are critical in addressing systemic bias and advancing equitable data practices. Health Data Research Network Canada (HDRN Canada) initiated an environmental scan to understand IDEA activities within its member organisations and identify opportunities to embed IDEA principles into its operations and data research approaches. The scan aimed to understand: 1) how IDEA activities are organised and sustained across the network; 2) the availability of resources and policies to support IDEA initiatives; and 3) gaps and opportunities for HDRN Canada to standardise and enhance IDEA efforts. A survey was distributed to 19 member organisations between December 2022 and February 2023, covering six domains of inquiry. Data were analysed using descriptive statistics and narrative synthesis, with insights from HDRN Canada's IDEA Team ensuring validity. Eighteen organisations participated, revealing significant variability in IDEA implementation. The findings highlight systemic gaps, including fragmented policies, insufficient training, a reliance on volunteer efforts, and informal mechanisms to ensure equitable use of disaggregated data.